Neglected Factors in the Problem of Normal Interest - Knight, F. H. (Quarterly Journal of Economics, 1916)
I. The nature of capital. Capital defined pragmatically as that for which interest is paid, 280. — Relation to entrepreneur function, 281. — Capital is value, 282. Relation to "rent, " 283. — II. The supply of capital, 284. — "Discounting the future" an erroneous explanation, 285. — Motives looking beyond the individual life, 286. — Value often produced specifically for capital use, in order to secure social position and power, 288. — The supply curve of capital, 291. — III. The demand for capital, 292. — There is "specific productivity, " 293. — In what sense, 294. — Convertibility of capital into rent-bearers, 295. — Summarized proposition, 298. — IV. The equilibrium of supply and demand, 299. — The conventional equilibrium of supply and demand refers to a unit of time only, 300. — Its application to capital unsound, 301. — Two separate problems, 303. — At a particular moment, no equilibrium, but an equilibrating action, 304. — The long period trend represented in three dimensions, 306. — In what sense the reasoning rests on "static" assumptions, 307. — A normal equilibrium of supply and demand and a normal rate of interest are wholly hypothetical, 309.